The effect of perceived trust of mobile banking services in Malaysia - Mahad, Murad; Mohtar, Shahimi; Othman, Abdul Aziz (International Academic Research Journal, 2015)
Mobile banking is defined as the usage of cellular phone or other mobile gadgets to conduct the tasks of online banking using a home computer, such as reviewing the balance in the account, transfer of money between accounts, find automated teller machine (ATM) and bill payments.The low penetration of mobile banking in Malaysia, especially in terms of adoption patterns is becoming the research interest, especially when compared to the total number of cellular telephone subscriptions.The penetration rate of mobile banking in Malaysia is still in the minority.The issue of trust beliefs that may affect the user’s intention to adopt the mobile banking services. Trust is a major aspect of everyday life.Some authors define trust as wish to depend on another entity and separating the concept of trust to some interconnected components trust such as trust beliefs (e.g., benevolence, efficiency, honesty, and predictability) believe the intention, trusting behaviors, disposition to trust, and the institution-based trust.